Cholinoreceptor autoantibodies in Sjögren syndrome (2007)
Previous studies have demonstrated that antibodies against cholinoreceptors of exocrine glands correlate with dry mouth in persons with primary Sjögren syndrome (pSS). The aim of the present investigation was to establish if serum IgG antibodies (pSS IgG) were able to interact with cholinoreceptors in rat submandibular gland-dependent stimulation of cyclooxygenase 2 (COX-2) mRNA expression and PGE2 production. Our findings indicated that pSS IgG-stimulating M3, M4, and M1 cholinoreceptors exerted an increase in COX-2 mRNA without affecting COX-1 mRNA expression and increased PGE2 production. Inhibitors of phospholipase A2, COX- s, L-type calcium channel currents, and Ca2+-ATPase from sarcoplasmic reticulum prevented the pSS IgG effect on PGE2 production. An ionophore of calcium mimicked pSS IgG action, suggesting a crucial role of calcium homeostasis in the cholinoreceptor-stimulated increase in PGE2 production. Moreover, the amounts of PGE2 in saliva and in sera from persons with pSS were significantly higher than in pre- or post-menopausal women. These findings illustrate the importance of autoantibodies to cholinoreceptors in the generation of chronic inflammation of target tissues in SS.